Intracavitary prophylactic treatment with interferon alpha 2b of patients with superficial bladder cancer is associated with a systemic T-cell activation. - Molto, L. (Nature Publishing Group, 1994)
The activation and proliferation of peripheral blood mononuclear cells (PBMNCs) are complex processes involving several surface molecules, cell secretion and response to cytokines. This paper investigates the immunomodulatory effect of prophylactic treatment with interferon alpha 2b (IFN-alpha 2b) upon the blastogenic response of PBMNCs from patients with superficial transitional cell carcinoma (STCC) of the bladder to mitogenic signals that interact with surface molecules [phytohaemagglutinin, PHA and anti-CD3 monoclonal antibodies, (MAbs)]. PBMNCs from the patients were studied prior to the transurethral resection (TUR) of the tumour, during the second month of prophylactic intravesical instillation of IFN-alpha 2b and 3 and 6 months after finishing the instillation treatment. The [3H]thymidine uptake of PBMNCs from 17 patients with STCC of the bladder after 5 days of PHA and anti-CD3 MAb stimulus was found to be significantly lower than that of healthy controls (P < 0.05). The addition of interleukin 2 (IL-2) to the culture medium did not correct this defective proliferative response to PHA and the anti-CD3 MAb. There were no significant differences between IL-2 production in PBMNCs from STCC patients after stimulation with PHA and in PBMNCs from healthy controls (P > 0.05). Patients without evidence of recurrence showed a significantly enhanced proliferative response in PBMNC to PHA and anti-CD3 MAb after intravesical prophylactic treatment with interferon-alpha 2b in the follow-up examinations 3 and 6 months after treatment (P < 0.01). However, three patients had evidence of tumour recurrence, and they showed no enhancement of the PBMNC proliferative response to these mitogens in the same examinations. In conclusion, the prophylactic intracavitary treatment of STCC with IFN-alpha 2b may induce a systemic immunomodulatory effect which is associated to the clinical evolution of the disease.